Building Sustainability Quality of English Education Department by Creating English Area - Fauzia Fauzia (Journal of Education and Learning (EduLearn), 2016)
Nowadays English is to be regarded as international languages in the world. In Indonesia as a part of South Asia, English has two functions as foreign and second language. In fact, English Language Education becomes more popular for all people in Indonesia. English area defines as a place which is able to support language learners to be more active in using English. This area is provided for learners to practice their English both of formal and informal. Creating English area as one of the ways to build a sustainable in English Language Education can be done in all levels. By using this method, language learner’s improvement will increase sharply, not only in the quantity but also in the quality. The reflection of a good quality will be seen in the quality of the language learners who can use English well along with comprehensive cross culture understanding knowledge.